2015
DOI: 10.1159/000437043
|View full text |Cite
|
Sign up to set email alerts
|

Use of Plastic Needles for Early Arteriovenous Fistula Cannulation

Abstract: Background: The native arteriovenous fistula (AVF) needs maturation before it can be used. Needling done before time may result in haematoma formation, miscannulation or even access loss. Methods: This retrospective study included 20 patients with AVFs punctured with fluoroplastic dialysis catheters within 30 days after access creation and 19 historical controls. Results: The time to first puncture was 2-29 days for the study group and 1-26 days for the control group. The incidences of haematoma were 16.7 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…Plastic cannulae have a symmetric round tip and four side holes within 0.5 cm from the tip and a 15G shaft ( Figure 1 ). Plastic cannulae are used during the first 2–4 weeks of cannulation of new or complex accesses for their lower risk of infiltration compared to metal needles; 11 , 13 , 14 , 17 , 18 their use can be extended in patients with high risk of infiltration. The primary reason to transition cannulae to metal needles is cost; they are 2–3 times more expensive than metal needles.…”
Section: Introductionmentioning
confidence: 99%
“…Plastic cannulae have a symmetric round tip and four side holes within 0.5 cm from the tip and a 15G shaft ( Figure 1 ). Plastic cannulae are used during the first 2–4 weeks of cannulation of new or complex accesses for their lower risk of infiltration compared to metal needles; 11 , 13 , 14 , 17 , 18 their use can be extended in patients with high risk of infiltration. The primary reason to transition cannulae to metal needles is cost; they are 2–3 times more expensive than metal needles.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound mapping of potential cannulation sites and ultrasoundguided cannulation in selected cases played an important role in the success of this study. 37,38 The use of plastic needles was also felt to contribute to the success of early cannulation 39,40 although not felt to be necessary in all patients, especially after the initial month of access use.…”
Section: Resultsmentioning
confidence: 99%
“…The above-mentioned study by Letachowicz et al (13) demonstrated successful cannulations with plastic cannulae in newly created AVF, without a negative influence on access survival. The authors stated that the study is limited by the small sample groups, not being randomised and by not including ultrasound-guided cannulations.…”
Section: Cannulation Of Newly Created Avfmentioning
confidence: 93%
“…A retrospective study carried out by Letachowicz et al (13) in a Polish dialysis unit compared the development of haematoma in 20 patients punctured with plastic cannula (17-gauge) with 19 patients punctured with metal needles (16-gauge). All patients had a newly created AVF and cannulations were performed within the first 30 days after creation.…”
Section: Needle or Plastic Cannula For Nocturnal Dialysismentioning
confidence: 99%